Effect of Loading Level and Span Length on Critical Buckling Load - Mohsen, Marwah A.; Abbas, Abdalnassre M.; Saadoon, Ahmed S. (Basrah Journal for Engineering Sciences, 2016)
An investigation was conducted to study the effect of loading level with respect to shear center and span length on lateral torsional buckling of steel I-section beams using linear and nonlinear finite element analysis available in ANSYS (version 12.0) computer program. The steel beams which have been studied included prismatic beams and linearly web- tapered beams with web tapering ratio of (0.5). The maximum height of all beams was 300 mm with span length of 4, 6 and 8 m. The critical buckling loads for prismatic and linearly tapered cantilever and simply supported beams subjected to point load and uniformly distributed load were determined. The results showed that, the bottom flange loading gives a buckling loads higher than that of the top flange loading with percentage increases of 148% and 155% for the linear and nonlinear analysis respectively for the prismatic beams. While for the tapered beams, these percentages increases were 61% and 67% respectively.